Diet and Coronary Heart Disease: Does Beef Fit In? - McDonald, Bruce E. (1989)
Changes in the fat and cholesterol content of retail cuts of Canadian beef over the past 16 years indicate that it is not necessary to limit beef in diets designed to meet the guidelines recommended at the recent Canadian Consensus Conference on Cholesterol. Recent studies have shown that the retail cuts of beef available in Canada today contain 20% to 60% less fat than previously reported in the Canadian nutrient data file. Cuts from the loin and hip region of the carcass (e.g., sirloin steak, round steak, and rump roast) that are trimmed of all visible fat are similar in fat, energy, and cholesterol content to chicken and fish.